Penguatan Kemandirian Ekonomi Kelompok PKK Desa Tirtomulyo dengan Inovasi Olahan Tape Singkong dan Pelatihan Pemasaran Produk - Arizo, Maya Bestari; Anggita Tri Hapsari; Mu’arifuddin Mu’arifuddin (Jurnal Bina Desa, 2025)
In achieving economic independence in society, a learning process is needed that can be implemented through training programs, skills development, and individual and community empowerment where the PKK enters the community. The Pancasila Women Agent work program provides training on MSMEs to PKK mothers with the aim of achieving economic strengthening carried out by women. There are three methods used, namely 1) Observation method, 2) Lecture method, 3) Training method. Wonokerso Hamlet PKK cadres had the idea to create a business with cassava after attending innovation training on making tape into sponge cake. Participants also learned about how to become a female Pancasila agent. Apart from that, Wonokerso Hamlet PKK cadre women were educated about product packaging and marketing, which can help them start a business.